Ethics and integrity in health and life sciences research - Koporc, Zvonimir (Advances in research ethics and integrity ;, 2018)
Life and health sciences and biomedical studies have developed rapidly over the last few decades raising previously unanticipated ethical concerns and questions. New and emerging technologies require novel approaches, protocols and raised awareness to ensure adequate levels of biosecurity and biosafety as well as the implementation of special measures to prevent their potential misuse or dual use.This volume brings together an international collection of prominent ethics experts in health and life sciences, with the aim of providing clear and comprehensive guidelines for the establishment of efficient ethical strategies related to current and emerging biotechnologies and health research.Important current topics in research ethics including CRISPR-Cas9 technologies, gene editing, 'big data' in healthcare and life sciences, nutrition in medicine among other topics have found their place in this volume. In addition, the volume discusses the prospects for the implementation of an international unification of ethical standards in life sciences.